Edukasi dan Implementasi Prinsip 3R (Reduce, Recycle dan Re-use) dalam Pengelolaan Sampah Rumah Tangga pada Warga Dusun IV Desa Muara Jalai Kec. Kampar Utara, Kab. Kampar - Ardiansyah Hamid; Anna Dhora; Razita Hariani; Niken Ellani Patitis; Fajar Aga Wandana (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2024)
Residents of Dusun IV Muara Jalai Village are currently experiencing problems related to waste, because a lot of household rubbish has been found dumped on the side of the road, in ditches, in the bushes and even in tributaries in the area. This situation certainly disrupts the cleanliness of the environment. Regarding these residents' problems, it is necessary to provide education to residents regarding household waste management. For this reason, the Kampar Polytechnic community service team (PKM) has provided education to residents regarding managing their household waste, namely by applying the 3R principle (Reduce, Re-Use and Recycle). There are many ways to apply the reduce principle in household waste management, such as bringing a shopping basket and plastic bag from home when shopping at the market, bringing a tumbler/drinking bottle when traveling and no longer using single-use products. Meanwhile, the principle of re-use can be applied, such as reusing used cans, used bottles to be reused later for other purposes, so they don't need to be thrown into the environment. The principle of recycling can be done by using used plastic bottles or used paper to make flowers, thus adding to the beauty of the house. Apart from that, make compost from household organic waste, such as onion skins, potato skins, vegetables, egg shells. The resulting compost can be used to fertilize home plants, such as flowers and vegetables. By applying the principles 3R in managing household waste, the amount of household waste will decrease further.